2014
DOI: 10.1074/jbc.m114.597880
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity-related Gene 5 Promotes Spine Formation in Murine Hippocampal Neurons

Abstract: Background: Plasticity-related gene 5 (PRG5) is prominently expressed in neurons, but its neuronal function is unknown. Results: PRG5 overexpression prematurely induces spine-like structures in immature hippocampal neurons, and PRG5 knockdown causes functionally relevant loss of excitatory synapses in dendrites of more mature neurons. Conclusion: PRG5 expression is involved in proper spine formation. Significance: We describe a new function of PRG5 in spinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(73 citation statements)
references
References 52 publications
10
63
0
Order By: Relevance
“…Overexpression of either LPPR1 or LPPR5 induces membrane protrusions in neuronal and non-neuronal cell lines (Broggini et al, 2010;Savaskan et al, 2004;Sigal et al, 2007). LPPR1 has been reported to promote neurite shaft protrusion in primary neurons (Velmans et al, 2013), whereas LPPR5 has been shown to induce neurite outgrowth (Broggini et al, 2010) and, more recently, to promote dendritic spine formation in hippocampal neurons (Coiro et al, 2014). The current findings suggest that LPPRs play putative roles in axonal outgrowth, regeneration and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 67%
“…Overexpression of either LPPR1 or LPPR5 induces membrane protrusions in neuronal and non-neuronal cell lines (Broggini et al, 2010;Savaskan et al, 2004;Sigal et al, 2007). LPPR1 has been reported to promote neurite shaft protrusion in primary neurons (Velmans et al, 2013), whereas LPPR5 has been shown to induce neurite outgrowth (Broggini et al, 2010) and, more recently, to promote dendritic spine formation in hippocampal neurons (Coiro et al, 2014). The current findings suggest that LPPRs play putative roles in axonal outgrowth, regeneration and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 67%
“…-Neuropathic pain (Choi et al, 2010); -Ischemic stroke (Savitz et al, 2006;Kimura et al, 2008); -Schizophrenia (Cunningham et al, 2006;Musazzi et al, 2011); -Behavioral dysfunctions (Santin et al, 2009); -Seizure (Elmes et al, 2004). (Suckau et al, 2019); -Neuronal differentiation (Spohr et al, 2008;E Spohr et al, 2011); -Survival and differentiation of neural progenitor cells (NPCs; Chun et al, 2002); -Neuronal hyperexcitability and neuro-plasticity (Broggini et al, 2010;Coiro et al, 2014);…”
Section: Receptors G Proteins Signaling Pathways Biological Functionsmentioning
confidence: 99%
“…Second, the accumulated LPA promotes the release of autotaxin (ATX) from astrocytes, further enhancing the glutamate concentration in the synaptic cleft (Thalman et al, 2018). Other evidence is also available showing that PRG-1 modulates LPA release in a non-cell-autonomous pattern, thus leading to an elevation of pre-synaptical glutamate vesicle release, as well as a series of alterations in structural plasticity such as filopodia formation, neurite extension, and brain reorganization after lesion (Broggini et al, 2010;Coiro et al, 2014).…”
Section: Lpa and Neuroplasticitymentioning
confidence: 99%
“…PRG-1 is expressed at postsynaptic sites of principal neurons and acts in a non-cell-autonomous fashion by controlling LPA in the synaptic cleft, which in turn stimulates presynaptic LPA receptors resulting in an increased release probability of glutamate vesicles at excitatory synapses (Tokumitsu et al, 2010;Trimbuch et al, 2009;Vogt et al, 2016). Previous studies have shown that various members of the PRG family play a role in regulating structural plasticity, including filopodia formation, neurite extension, and brain reorganization after lesion (Brauer et al, 2003;Broggini et al, 2010;Coiro et al, 2014;Peeva et al, 2006;Savaskan et al, 2004;Sigal et al, 2007;Velmans et al, 2013). However, using ionmobility enhanced data-independent label-free liquid chromatography (LC)-tandem mass spectrometry (MS), we have detected PRG-1 as a characteristic postsynaptic density (PSD) protein, while the other members of the PRG family were not found in a high-confidence PSD preparation (Distler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%